2007
DOI: 10.1007/s11631-007-0366-2
|View full text |Cite
|
Sign up to set email alerts
|

A decade of variation of COD in the Changjiang River (Yangtze River) and its variation trend analysis

Abstract: The average annual value of COD (chemical oxygen demand) fluxes of the Changjiang River (Yangtze River) and its main tributaries in the past decade (i.e., 1991-2000), has been evaluated. Based on the data from the Datong Hydrological Station (DHS), it was found that the Dongting Lake drainage basin contributed the greatest water discharge (35.8%) and COD flux (48.3%) among the main tributary drainage basins, followed by the Poyang Lake drainage basin with the contributions of 15.4% and 19.3% respectively. By t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…The concrete triangular pyramid belongs to a deformation body of concrete tetrahedron, which can maintain three feet to cling to the riverbed surface in any case. It has the advantage of good stability, good anti-erosion and good energy dissipation action, and its size can be calculated and determined according to the local conditions of water flow and river bed [3]. The large scale experiment was carried out in Nanguotou and Madu dangerous projects in 1997~1998, and the test block is 98.3cm high, the top part of foot has the diameter of 30cm, the volume of 0.27m 3 and the weight of 648kg.…”
Section: Root-stones Protection Technology Of Concrete Triangular Pyr...mentioning
confidence: 99%
See 1 more Smart Citation
“…The concrete triangular pyramid belongs to a deformation body of concrete tetrahedron, which can maintain three feet to cling to the riverbed surface in any case. It has the advantage of good stability, good anti-erosion and good energy dissipation action, and its size can be calculated and determined according to the local conditions of water flow and river bed [3]. The large scale experiment was carried out in Nanguotou and Madu dangerous projects in 1997~1998, and the test block is 98.3cm high, the top part of foot has the diameter of 30cm, the volume of 0.27m 3 and the weight of 648kg.…”
Section: Root-stones Protection Technology Of Concrete Triangular Pyr...mentioning
confidence: 99%
“…During the period of production operation of water and sediment regulation in 2007, other parts of dam 15 have been in greater danger, and the volume of emergency repair stones is 1176m 3 , and the total investment is 201,500 yuan, but the dam sections protected by tetrahedron-like concrete penetrating frames are without danger.…”
Section: Fig2 Comparison Of Root-stones Sections Between Dam 15 and D...mentioning
confidence: 99%
“…Liu et al [16] found that both climate and land use changes can lead to runoff change trends in the YZR. Wang et al [17] used the trend analysis and wavelet analysis methods to analyze the annual runoff change trend in Yangcun and Nuxia stations on the YZR from 1970 to 2012. The results showed that runoff presented an insignificant growth trend.…”
Section: Introductionmentioning
confidence: 99%
“…Morever,which give full play to the energy dissipation rate advantage for small unit overcurrent on stepped spillway to solve the energy dissipation problem [1] . Aeration can be effectively reduced cavitation damage, the buildings of flow with high head are generally set the aerator, prompting water aeration, thus reduced cavitation damage [2] . Take advantage of transverse contraction and vertical diffusion of asymmetric flaring gate pier and form a sheet longitudinally opened water tongue and aerated cavity between the stepped surface and the free jet which can realize fully aerated.…”
Section: Introductionmentioning
confidence: 99%